Kajian Tataniaga dan Strategi Penguatan Kelembagaan Pemasaran Komoditi Peternakan di Kecamatan Riung - David Januarius Djawapatty (Jurnal Kridatama Sains dan Teknologi, 2026)
This study analyses the marketing structure of livestock commodities and formulates strategies to strengthen livestock marketing institutions in Riung Subdistrict. A qualitative descriptive approach was employed, supported by primary field observations and secondary data comprising livestock potential records, regional statistics, and scientific literature. The analysis covered commodity mapping, marketing-channel identification, institutional diagnosis, and descriptive comparison between primary observations and secondary data. The findings indicate that pigs and goats function as sources of household liquidity, whereas buffaloes, horses, and cattle serve as high-value assets. However, marketing remains individual, dependent on collectors, and insufficiently supported by formal markets and local economic institutions. The study concludes that village marketing units, commodity clusters, price information, collective sales, quality standardisation, and partnerships with regular buyers are needed to improve farmers' bargaining position.